Purification and characterization of a thermophilic NAD+‐dependent lactate dehydrogenase from Moorella thermoacetica - Florian P. Rosenbaum; Volker Müller (FEBS Open Bio)
Oxidation of lactate under anaerobic dark fermentative conditions poses an energetic problem. The redox potential of the lactate/pyruvate couple is too electropositive to reduce the physiological electron carriers NAD(P)+ or ferredoxin. However, the thermophilic, anaerobic, and acetogenic model organism Moorella thermoacetica can grow on lactate but was suggested to have a NAD+‐dependent lactate dehydrogenase (LDH), based on enzyme assays in cell‐free extract. LDHs of thermophilic and anaerobic bacteria are barely characterized but have a huge biotechnological potential. Here, we have purified the LDH from M. thermoacetica by classical chromatography. Lactate‐dependent NAD+ reduction was observed with high rates. Electron bifurcation was not observed. At pH 8 and 65 °C, the LDH had a specific activity of 60 U·mg−1 for lactate oxidation, but NADH‐driven pyruvate reduction was around four times faster with an activity of 237 U·mg−1. Since lactate formation is preferred by the enzyme, further modifications of the LDH can be suggested to improve the kinetics of this enzyme making it a promising candidate for biotechnological applications.